2004
DOI: 10.1007/s00330-004-2288-2
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion CT in patients with advanced bronchial carcinomas: a novel chance for characterization and treatment monitoring?

Abstract: Advanced bronchial carcinomas by means of perfusion and peak enhancement using dynamic contrast-enhanced multislice CT are characterized. Twenty-four patients with advanced bronchial carcinoma were examined. During breathhold, after injection of a contrast-medium (CM), 25 scans were performed (1 scan/s) at a fixed table position. Density-time curves were evaluated from regions of interest of the whole tumor and high- and low-enhancing tumor areas. Perfusion and peak enhancement were calculated using the maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 25 publications
5
72
1
1
Order By: Relevance
“…This implies an increase in pulmonary blood supply with growing tumor size. Our findings correspond reasonably to the results of the study by Kiessling et al, 37 who found lower perfusion in tumors larger than 50 mm 3 , using a bronchial arterial system analysis. Tumor volume certainly reflects the actual tumor size more exactly than does the maximum diameter alone.…”
Section: Nguyen-kim Et Alsupporting
confidence: 93%
“…This implies an increase in pulmonary blood supply with growing tumor size. Our findings correspond reasonably to the results of the study by Kiessling et al, 37 who found lower perfusion in tumors larger than 50 mm 3 , using a bronchial arterial system analysis. Tumor volume certainly reflects the actual tumor size more exactly than does the maximum diameter alone.…”
Section: Nguyen-kim Et Alsupporting
confidence: 93%
“…and PE (peak enhancement) parameters between SCLC and NSCLC cases [1]. We also did There were also some factors with a negative influence on CT perfusion in our study.…”
Section: First-pass Perfusion Ct In Lung Cancersupporting
confidence: 48%
“…The use of non-invasive functional imaging methods in the detection, staging and follow-up of lung cancer has gradually become routine in clinical applications [1]. Perfusion CT is one of these methods and is a promising technique that allows functional evaluation of tissue vascularity [2].…”
Section: Introductionmentioning
confidence: 99%
“…(Table 1) Location of Lung Cancer and Perfusion Parameters Central tumour was defined as having contact to the hilum, whereas all other tumours were considered peripheral. 6 All SCLC were centrally located (2/2 i.e. 100%), whereas SCC (11/16 i.e.68.75%) and Adenocarcinoma (7/10 i.e.…”
Section: Ct Perfusion Parameters In Different Subtypes Of Lung Cancermentioning
confidence: 96%
“…14 Keisling et al and Li Y et al also observed significantly higher perfusion in smaller tumours than larger one. 6,15 Several mechanisms have been advocated to explain why large tumours are poorly vascularized and have a poor prognosis. The decrease in micro vessel density (MVD) reflects the inability of tumour neovascularization to support the fast proliferation of the tumour cells, leading to a reduced vascular supply, resulting in necrosis, which is very frequent in larger lesions.…”
mentioning
confidence: 99%